Homophilic protein interactions facilitate bacterial aggregation and IgG-dependent complex formation by the Streptococcus canis M protein SCM. Issue 1 (1st January 2019) - Nerlich, Andreas; Lapschies, Antje-Maria; Kohler, Thomas P.; Cornax, Ingrid; Eichhorn, Inga; Goldmann, Oliver; Krienke, Petra; Bergmann, Simone; Nizet, Victor; Hammerschmidt, Sven; Rohde, Manfred; Fulde, Marcus
ABSTRACT: Streptococcus canis is a zoonotic agent that causes serious invasive diseases in domestic animals and humans, but knowledge about its pathogenic potential and underlying virulence mechanisms is limited. Here, we report on the ability of certain S. canis isolates to form large bacterial aggregates when grown in liquid broth. Bacterial aggregation was attributed to the presence and the self-binding activity of SCM, the M protein of S. canis, as evaluated by bacterial sedimentation assays, immunofluorescence- and electron microscopic approaches. Using a variety of truncated recombinant SCM fragments, we demonstrated that homophilic SCM interactions occur via the N-terminal, but not the C-terminal part, of the mature M protein. Interestingly, when incubated in human plasma, SCM forms soluble protein complexes comprising its known ligands, immunoglobulin G (IgG) and plasminogen (Plg). Co-incubation studies with purified host proteins revealed that SCM-mediated complex formation is based on the interaction of SCM with itself and with IgG, but not with Plg or fibrinogen (Fbg), well-established constituents of M protein-mediated protein complexes in human-associated streptococci. Notably, these soluble, SCM-mediated plasma complexes harbored complement factor C1q, which can induce complement breakdown in the periphery and therefore represent another immune evasion mechanism of SCM.